DESCOBRINDO O ENSINO DA ASTRONOMIA NAS ESCOLAS DE ENSINO FUNDAMENTAL DE BREVES-PARÁ - FAVACHO, Luciano Gonçalves (2024)
This study is an experience report. The result of studies carried out in the project “Introduction to the Astronomy World in Marajó Island – Breves City" and the objective of analyzing the Astronomy Teaching at elementary schools from Breves City – Pará Estate. In addition to the report of actions of project, the presented results, based on the data collected and the theories studied, among them: Afonso (2006), which exposes the history of indigenous astronomy; Faria (2009), Veiga, Ponte Neto et all (2015), Moraes and Chiaradia (2007), Steiner (2009), presents the history of astronomy and its teaching; Langhi and Nardi (2009, 2010), Bretones (1999), Daminele (2009), Daminele and Steiner (2010), Bizzo (2009) discuss the teaching of astronomy and teacher training to work the subject in basic education. All serve as a basis for the project reported and for the research carried out in it. The methodology adopted was the case study in elementary schools. The studied people of the project were active teachers in the initial and final grades from Elementary Schools. The application of open questionnaires had used for data collection. The results indicate a great need for projects and continuing education in the area of astronomy that will fill the shortcomings on astronomy teaching presented by the teachers researched. Pointing suggestions for the improvement on Astronomy teaching in Elementary School from Breves, this work does not exhaust the needs of new research on the subject, still little known and worked in our region, both in Basic Education and in Higher Education